Advanced biology principles and applications - Clegg, C. J.; Mackean, D. G. (Donald Gordon) (John Murray, 2000)
This A Level Biology textbook covers all the requirements of the AS and A2 Biology specifications. This second edition has been updated to include: revisions to the content to reflect changing AS and A Level specifications; revised chapters on the underlying principles of ecology and modern biotechnology and genetic engineering; updated examination questions from recent past papers; and the use of full colour throughout.